Experimental Model Systems to Define Mechanisms of Immune-Mediated Blood Brain Barrier Disruption in Acute Disseminated Encephalomyelitis (ADEM) and Acute Hemorrhagic Leukoencephalitis (AHLE) - Johnson, Holly L.; Pirko, Istvan; Johnson, Aaron J. (IntechOpen, 2011)
None